2020
DOI: 10.2174/1381612826666200523172334
|View full text |Cite
|
Sign up to set email alerts
|

AMPK and its Activator Berberine in the Treatment of Neurodegenerative Diseases

Abstract: : Neurodegenerative disorders are heterogeneous diseases associated with either acute or progressive neurodegeneration, causing the loss of neurons and axons in the central nervous system (CNS), showing high morbidity and mortality, and there are few effective therapies. Here we summarized the energy sensor adenosine 5‘-monophosphate (AMP)-activated protein kinase (AMPK) and its agonist berberine can combat the common underlying pathological events of neurodegeneration including oxidative stress, neuroinflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 150 publications
0
13
0
Order By: Relevance
“…Previous studies have found that BBR also lowers blood sugar, corrects blood lipid disorders, reduces the production of inflammatory factors, and inhibits the release of endotoxin. It has certain pharmacological effects on metabolic syndrome, digestive-system diseases, cardiovascular diseases, tumors, and mental disorders ( 10 ). BBR has been used to treat type 2 diabetes ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that BBR also lowers blood sugar, corrects blood lipid disorders, reduces the production of inflammatory factors, and inhibits the release of endotoxin. It has certain pharmacological effects on metabolic syndrome, digestive-system diseases, cardiovascular diseases, tumors, and mental disorders ( 10 ). BBR has been used to treat type 2 diabetes ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…AMPK activation is also an essential component of the adaptive response to cardiomyocyte stress that occurs during myocardial ischemia [ 47 ]. Therefore, pharmacological activation of AMPK can be applied as a cardioprotective strategy for the treatment of myocardial infarction [ 48 ]. Depending on the presence of downstream targets of AMPK, such as mTOR, SIRT1, Nrf2, NF-κB, PI3K/Akt, and p38 MAPK, AMPK can exert opposite functions in different cells.…”
Section: Discussionmentioning
confidence: 99%
“…Aging is also associated with a decline in AMPK activation in response to various insults [41,46]. In either case, AMPK has been considered a potential therapeutic target for metabolic diseases, including type 2 diabetes, as well as other age-associated diseases [33,[47][48][49]. Because previous studies have revealed that AMPK is an important regulator of the GAPDH nuclear translocation in young HDFs [50], we hypothesized that the increased AMPK activity with senescence may change the intracellular localization of GAPDH, which might play a critical role in age-related functional decline and diseases.…”
Section: Agingmentioning
confidence: 99%
“…Similarly, activation of AMPK by berberine reduces activated microglia; neutrophil infiltration; and IL-1beta, IL-6, CCL2, and CXCL2 production, which occur after traumatic brain injury [34]. In both cases, AMPK prevented the activation of the TLR4/NF-kB signaling pathway [31,34,35]. AMPK also inhibits lipopolysaccharide (LPS)-induced expression of proinflammatory cytokines (TNF-alpha, IL-1beta, and IL-6) by attenuating LPS-induced, TLR4-mediated NF-kB activation [36][37][38].…”
Section: Metformin and Neuroinflammationmentioning
confidence: 99%